Pengaruh Promosi, Harga dan Produk Minat Beli Konsumen Di Langsa Town Square - Ika Syafiani; Rahmi Meutia; Najihatul Faridy (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
This research aims to determine the influence of promotion (X1), price (X2), produk (X3) on interest (Y) partially and simultaneously on the performance of MSMEs in Langsa City. The sample in this research consisted of 100 respondents. The partial research . promotion variable is 0.019 < alpha 0.05, meaning promotion has a significant influence on buying interest at Langsa Town Square. The research results show that the significance value of the price variable is 0.019 < alpha 0.05, meaning that price has a significant influence on buying interest at Langsa Town Square. Product variable is 0.046 < alpha 0.05, meaning that the product has a significant influence on buying interest at Langsa Town Square. The research results show simultaneously (as a whole) promotion (X1), price (X2) and produk (X3) on the purchase interest variable (Y) where the significance value is 0.000